2019
DOI: 10.1111/his.13818
|View full text |Cite
|
Sign up to set email alerts
|

Handling and reporting of pelvic lymphadenectomy specimens in prostate and bladder cancer: a web‐based survey by the European Network of Uropathology

Abstract: Aims: Pathological evaluation of lymphadenectomy specimens plays a pivotal role in accurate lymph node (LN) staging. Guidelines standardising the gross handling and reporting of pelvic LN dissection (PLND) in prostate (PCa) and bladder (BCa) cancer are currently lacking. This study aimed to establish current practice patterns of PLND evaluation among pathologists. Methods and results: A web-based survey was circulated to all members of the European Network of Uropathology (ENUP), comprising 29 questions focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…LN metastasis is a predictor of poor outcome in bladder UC [17]. LN counts and the resulting LND likely suffer from the lack of established standards in gross handling, counting and reporting of PLND specimens [8][9][10]. The pathologist's practical approach is to palpate and dissect LN from the surrounding adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LN metastasis is a predictor of poor outcome in bladder UC [17]. LN counts and the resulting LND likely suffer from the lack of established standards in gross handling, counting and reporting of PLND specimens [8][9][10]. The pathologist's practical approach is to palpate and dissect LN from the surrounding adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A further issue is a frequently requested minimum number of LN for diagnosis. All these measures suffer from the lack of established standards in gross handling, counting, and reporting of PLND specimens [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The minimum number of LN needed for more accurate bladder cancer pN staging is still uncertain. To date, nine LN have been considered sufficient [7], but in routine clinical practice it is usual to obtain from 4 to 16 [6], and the American Joint Committee on Cancer recommends more than 12 LN [8]. Nevertheless, in general, authors agree that as more tissue is studied, more LN are found.…”
Section: Discussionmentioning
confidence: 99%
“…The number of LN detected by the pathologist may depend on the extent of the LDN [3], the inter-individual variability among patients [4], and the handling and interpretation of the pathological specimen [5]. Currently, consensus is lacking on the optimal handling and reporting of LDN specimens [6], which may explain differences in the interpretation between an LN and a simple lymphoid aggregate and in the methodology used to evaluate LN and the corresponding final count [5]. LDN pathological dissection is one variable that can be standardized.…”
Section: Introductionmentioning
confidence: 99%